Posterior Reversible Encephalopathy Syndrome (PRES) Associated with Eclampsia in Adolescent Pregnancy: Case Report - Podder, Priyanka; Saha, Joysree (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Posterior Reversible Encephalopathy Syndrome (PRES) is a rare complication of pre-eclampsia and eclampsia. It is a reversible syndrome characterized by headache, seizure, altered consciousness and loss of vision associated with white matter changes on imaging. The lesions predominantly in the posterior cerebral hemispheres in PRES are thought to be due to vasogenic oedema, PRES is best managed by monitoring and treatment in the setting of a neuro-intensive care unit. Prognosis is usually benign with complete reversal of symptoms, if adequate treatment is immediately initiated. Delay in diagnosis and treatment may lead to permanent neurological sequelae. This study reports a 18-year-old woman on her 4th post operative day following caesarean section presented with headache, dimness of vision, and repeated attack of seizure. The MRI of brain report showed abnormal signal intensity in the white matter of the occipital and parietal lobes. She was treated successfully with anti-hypertensives, anticonvulsants, and supportive care in ICU. PRES syndrome should always be considered in women with acute hypertension disorders associated with epileptic seizures or other neurological symptoms during pregnancy and in the postpartum. Early diagnosis is important to prevent permanent neurologic damage and mortality. Bangladesh J Obstet Gynaecol, 2023; Vol. 38(2): 103-106